If you want to lose weight go to the moon! / Ahmad Lutfi Anis - Anis, Ahmad Lutfi
Physics is undoubtedly one of the most fundamental of all sciences. Yet there is still the common perception, especially among school and university students, that understanding physics can be a ghastly experience. Everyone points the finger at mathematics for their difficulties in comprehending the subject, although the two disciplines merely complement each other. In fact, learning physics is about grasping the fundamental concepts, observing how they apply to nature, and using mathematics as a tool to make theories more believable! This book is a short journey through the philosophical mind of an eccentric lecturer who wants to diffuse the misconception about physics by simple storytelling using analogies, aphorisms, quotes, and polite sarcasms. While the theories covered by this book are limited to basic mechanics (nothing fancy), the aim is to 'bring to life' topics which many may normally find rather dreary. Perhaps there will be readers who would identify with the humour this book provides, and realize that while nothing beats ice cream, learning physics can be no less enjoyable.